Kaidah Sosial dan Hukum dalam Teks Manawa Swarga dan Konteksnya Pada Masyarakat Bali di Kabupaten Klungkung - I Wayan Wastawa; I Ketut Sudarsana (Jayapangus Press, 2020)
Bali is known for its valuable traditions and customs from pre-Hindu times to the present. Social facts, that the more widespread social problems occur that are not directly proportional to the social and legal rules in the lontar text and customs in Bali. The purpose of this paper is to examine the social norms and legal norms contained in the Manawa swarga text and its context in Balinese society in Klungkung Regency. This paper uses primary data and secondary data, with methods of observation, text search, interviews and literature study. Data analysis techniques, the process of collecting data, classification, display data, interpretation and conclusions. The finding is that there is a relationship between the contents of the Vedic scriptures, Manawadhamasastra, Manawa Swarga, and customary law (awig-awig) in Bali. Each of them describes the Chess of Varna or four classes of professions, which is contained in Ṛgveda: 10.90.12, Manawadharmasastra / Manu Smrtih. Pratamo'dhyayah I.31 Manawa Swarga text article 189. The contents of the Manawa Swarga text are still relevant to current social phenomena, specifically regarding the homosexual legal norms, hate speech